2013
DOI: 10.1164/rccm.201302-0247oc
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Soluble Receptor for Advanced Glycation Endproducts Is a Biomarker of Emphysema and Associated with AGER Genetic Variants in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Lower circulating sRAGE levels are associated with emphysema severity and genetic polymorphisms in the AGER locus are associated with systemic sRAGE levels. Clinical trial registered with www.clinicaltrials.gov (NCT 00413205 and NCT 00292552).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
133
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(151 citation statements)
references
References 47 publications
16
133
1
1
Order By: Relevance
“…In a GWAS of quantitative imaging phenotypes in smokers with and without COPD, we identified genome-wide significant associations with loci previously shown to be associated with COPD or with spirometric measures related to airflow limitation, including the 15q25, HHIP, and AGER loci, the latter also identified in association with emphysema in a general population sample (15) and with emphysema and sRAGE levels in COPD (42). We also describe a genome-wide association with emphysema and variants near SERPINA10 and show that this association is in strong linkage disequilibrium with the Z-allele of SERPINA1 and not due the presence of PI ZZ individuals.…”
Section: Discussionmentioning
confidence: 88%
“…In a GWAS of quantitative imaging phenotypes in smokers with and without COPD, we identified genome-wide significant associations with loci previously shown to be associated with COPD or with spirometric measures related to airflow limitation, including the 15q25, HHIP, and AGER loci, the latter also identified in association with emphysema in a general population sample (15) and with emphysema and sRAGE levels in COPD (42). We also describe a genome-wide association with emphysema and variants near SERPINA10 and show that this association is in strong linkage disequilibrium with the Z-allele of SERPINA1 and not due the presence of PI ZZ individuals.…”
Section: Discussionmentioning
confidence: 88%
“…Cheng et al (2013) investigated 21 SNPs in the AGER locus with sRAGE levels and found that the G82S polymorphism of the RAGE gene was associated with circulating levels of sRAGE levels in COPD patients. Young et al (2011b) found that the minor allele (T allele or CT/TT genotype) of the G82S polymorphism of RAGE was more commonly found in smokers who did not have COPD compared with those with COPD in a Western population.…”
Section: Discussionmentioning
confidence: 99%
“…sRAGE is the resulting product of both alternative splicing (esRAGE) and cleavage of membrane-bound RAGE [101,102] . Circulating levels of sRAGE are decreased in COPD patients when compared to healthy smoking controls and appear to be associated with emphysema independently of COPD severity [65] . In addition to the association of sRAGE with emphysema, two SNPs in the gene coding for RAGE (AGER locus) were significantly associated with systemic sRAGE levels.…”
Section: Prioritized Copd Protein Biomarkersmentioning
confidence: 90%
“…Accumulating evidence indicates that chronic inflammatory and immune responses play key roles in the development and progression of COPD [60,61] . In this respect, most of the potential biomarkers included in our list are proteins involved in inflammation or the immune response such as CRP, IL-6, beta defensin 2, among many others [25][26][27]29,36,37,54,[62][63][64][65][66][67][68][69][70][71][72][73][74] . One of the main causes leading to COPD is chronic smoking which exposes the respiratory tract to reactive oxygen species, resulting in oxidative stress and injury (which in the last instance leads also to inflammation) [59,75] .…”
Section: Copd Protein Biomarkersmentioning
confidence: 99%